EFFICIENCY OF MEDICINES AT VARROATOSIS OF BEES IN THE WEST KAZAKHSTAN REGION [Text] - Dosmukhambetov, T.R.; Karmaliyev, R. S. (Science and education №4, 2018)
Varroatosis – the most widespread disease caused by Varroa destructor mite and proceeding all the year round. The mite causes extensive economic damage which consists of death of brood, adult working bees and loss of production. There are a large number of methods of fight against this disease. The most radical measure of fight against varroatosis of bees is application of chemotherapeutic medicines. Today, at the fight against varroatosis of bees there are applied chemical medicines incorporating the following active ingredients: fluvalinate, flumethrin, akrinatrin, formamines, coumaphos, organic acids, essential oils and medicinal herbs. Also, it is noted that the safest concerning activity of bees are phytogenesis medicines. The purpose of our researches - studying of dynamics of contamination of bees with varroatosis during the summer period and studying of acaricide medicines efficiency. Varroatosis is present throughout the beeyards of Zelenovsky area. Average invasion extensiveness was 10,08%. The greatest efficiency at varroatosis of bees was shown by Apidez medicine. Its extensity efficiency was 100%. All bee-families of the test group where this medicine has been applied are completely exempted from varroa tick. After application of medicines, no deviations in their clinical state were revealed at the test groups.Варроатоз – наиболее распространенное заболевание, вызываемое клещом Varroa destructor и протекающее круглогодично. Клещ наносит большой экономический ущерб, который складывается из гибели расплода, взрослых рабочих пчел и потери продукции. Существует большое количество методов борьбы с данным заболеванием. Наиболее радикальной мерой борьбы против варроатоза пчел является применение химиотерапевтических препаратов. На сегодняшний день при борьбе с варроатозом пчел применяют химические препараты, имеющие в своем составе следующие действующие вещества: флувалинат, флуметрин, акринатрин, формамины, кумафос, органические кислоты, эфирные масла и лекарственные растения.
Keywords: рк; научный журнал; отечественное издание; периодическое издание; журнал кксон; ветеринария; варроатоз; клещи; пчеловодство; болезни пчел; varroatosis; apidez; fumisan